La Via Campesina Calls for the End of the WTO - David, Jenny (Glendon Journal of International Studies, 2015)
The purpose of this paper is to better understand global civil society and how the activities of rising social movements contribute in shaping it. It offers a glimpse of the diverse theories of globalization that shed light on the way in which scholars apply a specific theory to frame their analysis on various aspects of global civil society. The theoretical foundation is further used to perform an analysis of La Via Campesina, an international peasant movement which, this paper argues, supports the pessimistic globalist perspective. This social movement essentially brings together people from all around the world who share common values in order to promote and materialize its primary mission: food sovereignty. This paper assesses the most important goals of this social movement’s through the specific conceptualization of global civil society as described by both authors Hugh Mackey (2004) and Patrick Hayden (2007). Finally, it expresses how the International Studies lens may unlock new avenues for such transnational social movements to understand and face their challenges. Le but de cet essai est de mieux comprendre la société civile internationale et la façon dont les activités des mouvements sociaux ont contribués à la façonner. Il offre d’abord une introduction des diverses théories de la globalisation qui permet ensuite d’éclairer le lecteur sur la façon dont les spécialistes appliquent une théorie particulière à la formulation d’hypothèses sur des aspects variés de la société civile internationale. La base théorique est utilisée ultérieurement afin de performer une analyse de La Via Campesina, un mouvement international de paysans qui, selon l’argumentaire de cet essai, supporte la perspective globaliste pessimiste. La Via Campesina rassemble des gens des quatre coins du monde qui partagent des valeurs communes afin de promouvoir et de matérialiser sa mission la plus chère : la souveraineté alimentaire. Cet essai jauge les plus importants buts de ce mouvement social à travers les conceptualisations de la société civile internationale spécifiques aux auteurs Hugh Mackey (2004) et Patrick Hayden (2007). Il exprime enfin de quelle manière la lentille des Études internationales permet de débloquer de nouvelles avenues pour comprendre et répondre aux défis de tels mouvements sociaux transnationaux.